(untitled) (Teaching and Learning Inquiry, 2021)
In the wake of policy, technology, and ideological disruptions in Western higher education, it is in universities’ interests to improve the quality of their learning and teaching to meet changed expectations. In some countries, particularly anglophone countries such as Australia, Canada, New Zealand, and the United Kingdom, the medium for this improvement is often professional development of academic staff provided through a Graduate Certificate in Higher Education (GCHE). This paper presents mixed methods research conducted at an Australian University. It addresses the questions of how a GCHE contributes to teaching quality and the Scholarship of Teaching and Learning (SoTL) from the perspective of course participants and their educators in the context of a university wide strategy to promote a culture of excellence in learning and teaching. Data and analysis indicate significant benefits to academic staff, their students, and the host institution from completion of a GCHE. However, tensions around academic workloads, compulsion, and some contradictions in espoused educational values and managerialist impositions emerge in these advancements. The educators in the GCHE (academic developers) were sometimes caught in the crossfire. Their reflections on this experience are included in the data and analysis.